Systematic Identification of H274Y Compensatory Mutations in Influenza A Virus Neuraminidase by High-Throughput Screening - Wu, Nicholas C. (American Society for Microbiology, 2013)
Compensatory mutations contribute to the appearance of the oseltamivir resistance substitution H274Y in the neuraminidase (NA) gene of H1N1 influenza viruses. Here, we describe a high-throughput screening method utilizing error-prone PCR and next-generation sequencing to comprehensively screen NA genes for H274Y compensatory mutations. We found four mutations that can either fully (R194G, E214D) or partially (L250P, F239Y) compensate for the fitness deficiency of the H274Y mutant. The compensatory effect of E214D is applicable in both seasonal influenza virus strain A/New Caledonia/20/1999 and 2009 pandemic swine influenza virus strain A/California/04/2009. The technique described here has the potential to profile a gene at the single-nucleotide level to comprehend the dynamics of mutation space and fitness and thus offers prediction power for emerging mutant species.